Perbandingan Stabilitas Fisik Formulasi Farmasetika 5% dan 10% Zingiber officinale: Sifat Organoleptik, pH, Daya Sebar, dan Daya Lekat pada Kondisi Uji Cycling Test - Putri Jati Utami; Triasari Oktavriana; Prasetyadi Mawardi (Journal of Pharmaceutical and Sciences, 2026)
Ginger (Zingiber officinale) has demonstrated anti-inflammatory and immunomodulatory potential, supporting its development as a topical agent for inflammatory skin diseases such as psoriasis, but its physical stability must first be confirmed to ensure that therapeutic effects can be attributed to the active compound rather than formulation degradation. This study aimed to evaluate and compare the physical stability of 5% (F1) and 10% (F2) ginger extract salves through organoleptic, pH, spreadability, and adhesion testing under cycling test conditions consisting of six cycles of 24 hours at 4 °C followed by 24 hours at 40 °C, with three replicates per formulation assessed at baseline and after each cycle. Data were analyzed using paired t-tests for within-formulation comparisons and independent t-tests for between-formulation comparisons. Both formulations retained their characteristic ginger aroma, brown color, semi-solid consistency, and homogeneity throughout all six cycles. The pH of F1 ranged from 4.31 to 4.33 and F2 remained at 4.48, with no significant change between cycle 0 and cycle 6 (p > 0.05). Spreadability ranged from 4.79–4.84 cm for F1 and 5.20–5.33 cm for F2, while adhesion time was 4.78–4.82 s for F1 and 3.12–3.14 s for F2. The 10% formulation showed significantly higher pH and spreadability and significantly shorter adhesion time than the 5% formulation (all p<0.001), reflecting concentration-dependent rheological behavior. Both formulations demonstrated acceptable physical stability with all parameters within pharmacopoeial limits, supporting their use in subsequent in vivo efficacy studies for psoriasis.